Combination principle of hybrid sources and three typical types of hybrid source heat pumps for year-round efficient operation. (15th February 2020) - Li, Xianting; Lyu, Weihua; Ran, Siyuan; Wang, Baolong; Wu, Wei; Yang, Zixu; Jiang, Sihang; Cui, Mengdi; Song, Pengyuan; You, Tian; Shi, Wenxing
Abstract: Traditional single source heat pump systems, e.g., air source heat pump (ASHP) and ground source heat pump (GSHP), cannot work efficiently in the whole year. To develop an energy-efficient heat pump system for year-round operation, temperature grades of common natural energies are compared with each other. Based on the comparison, the combination principle of hybrid sources with complementary characteristics is discussed firstly. Then three typical types of heat pumps with hybrid sources are selected as representatives to show how to take full advantages of different heat sources or sinks for energy-efficient operation and how to extend functions of hybrid source heat pumps for new solutions to the disadvantages of conventional heat pumps. Finally, the annual performances of these three selected types of hybrid source heat pump systems for three corresponding specific cases are simulated by TRNSYS. The results show that hybrid source heat pump systems can maintain nearly the same heating capacity as they do without frost during the defrosting period; maintain energy-efficient year-round cooling with no risk of freezing during winter; keep the thermal balance of soil and maintain reliable cooling and heating over long periods of operation; fully utilize solar radiation of different intensities; and achieve year-round energy-efficient performance. In contrast to a conventional ASHP and GSHP system, the energy saving rate of a typical hybrid source heat pump system is approximately 15%, and the payback period is approximately five years. Hybrid source heat pumps provide a way to match multiple heat sinks/sources for different levels of building demand in different climates. Graphical abstract: Image 1030 Highlights: The HSHP can fully combine the advantages of different kinds of natural energies. The HSHP achieves almost no decline in heating capacity during defrosting period. The HSHP achieves the thermal balance of soil over long periods of operation. The HSHP fully utilizes solar radiation of different intensities. The HSHP operates efficiently year-round, and the payback period is about five years.